Programas radiales y educación ambiental - Jurado Robalino, Génesis Michelle (2023)
In this research work, an analysis of the programming grids of the radios in the city of Guayaquil was carried out, with the objective of analyzing the existence of environmental education programs in the programming. To achieve this process, we began by investigating the history of radio, its origins in Ecuador and how it has evolved at present focusing on the city of Guayaquil, after which we inquired about environmental radio programs, that is, we collected theoretical information on the background of these programs with a focus on environmental care in the port city. After defining the approach and the background of the research, we proceeded to implement the data collection instruments, these were qualitative and quantitative, therefore the research is mixed, this helped to provide a work with data that faithfully support what was investigated............